Circular Economy and Integrated Pest Management in Rice Farming: A Model for Sustainable Agricultural Education - Rita Parmawati; Soemarno; Setyo Widagdo; Indra Purnama Putra (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a circular economy model to promote the sustainability of Integrated Pest Management (IPM)-based rice farming in Kediri Regency, Indonesia. Agricultural systems in the region face persistent challenges, including environmental degradation and chemical overuse. By adopting key principles of the circular economy—such as reduce and recycle—this research offers a practical solution to optimize resources and minimize ecological impact in rice farming systems. A mixed-methods approach was employed, combining sustainability assessment tools and structural equation modeling to evaluate and validate the model. Data were collected from 100 purposively selected IPM-oriented farmer groups. The results indicate that the "reduce" (β = 0.642) and "recycle" (β = 0.510) principles have the strongest influence, supported by high adoption rates (83% and 76%, respectively), while the "reuse" principle shows the lowest impact (β = 0.206), hindered by institutional and infrastructural limitations. The model demonstrates adequate reliability and convergent validity, confirming its applicability for sustainable farming evaluation. Overall, this study concludes that integrating circular economy strategies within IPM-based rice farming provides a viable pathway for ecological sustainability and offers an educational framework to foster environmental literacy. Strategic policy support and educational interventions are essential to scale up these practices across agricultural systems.